Processos e percursos de aprendizagens: o protagonismo das crianças do ensino fundamental I por meio da Tic - Zanocini, Marcia Regina Rezende (2018)
The theme of this dissertation involves the enhancement of knowledge about the use of Information and Communication Technologies (ICT) as a support for pedagogical practices, from the processes and learning pathways in Elementary School I, initial grades. The complex daily life that challenges us as educational professionals requires to be watched with care. In this way, it is questioned: To the extent that the children are stimulated to enjoy the autonomy in the construction of their learning, how this construction process happens with the use of the ICT? To answer the question, it was defined as the main objective of the research, to analyze the protagonism and the authorship of the student in his learning course through the Information and Communication Technologies. The specific goals were: a) to investigate how teachers understand ICT and uses it in their pedagogical practices; b) to identify facilities and difficulties encountered by teachers related to the pedagogical practices and ICT; c) to evaluate how students appropriate knowledge resulting from pedagogical practices, propitiated by the use and construction of learning resulting from the Information and Communication Technology. As a theoretical contribution, it was sought subsidies in authors such as Vygotsky, Kenski, Behrens, Relvas, Cosenza and Guerra, among others. The school defined for the research was selected through the insertion of the researcher in the Municipal Network of Curitiba and in the school. The research consisted of a qualitative study, using different instruments such as: a script of interviews with six teachers, the application of questionnaires to thirty students from the 4th grade and the application of an experimental activity, as well as observations, through which it was analyzed the daily routine of the school. The main results point to the need for a redefinition of the use of ICT in schools, from a continuous development of teachers to work with ICT, reviewing concepts and resizing actions, so that there is a possible transformation in pedagogical practice. In regards to the protagonism and authorship of the students, it is understood that it still needs to be highly stimulated among the teachers, because this one, remains little present in the classroom. It must be understood that the adult / teacher is a key factor in the development of the course, authorship and learning process of students, as well as the construction of permanent dialogue for the build up of knowledge and incentives, which are essential for training.